2019
DOI: 10.1002/advs.201900399
|View full text |Cite
|
Sign up to set email alerts
|

New Metallic Ordered Phase of Perovskite CsPbI3 under Pressure

Abstract: Pressure‐induced electronic structure transition from insulating phase to metal state is a potential new paradigm for halide perovskites. The metallization based on these materials may afford a novel motif toward realizing new electronic properties even superconductivity phenomenon. Herein, how static compression modulates the crystal and electronic structure of typical perovskite semiconductors cesium lead iodine (CsPbI 3 ) by both experimental and theoretical studies is reported. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 30 publications
4
52
1
Order By: Relevance
“…However, a dramatic increase of this contribution under a −8% compressive strain is observed, which is also reflected in Figure under a −8% strain, where the CBM is shown in green color as the I electrons contribute the most to it. This is similar to the pressure-induced electronic structure transition from the insulating phase to the metal phase reported in Liang et al , showing a noticeably enhanced I-5p orbital contribution in the CBM under 50 GPa.…”
Section: Resultssupporting
confidence: 90%
“…However, a dramatic increase of this contribution under a −8% compressive strain is observed, which is also reflected in Figure under a −8% strain, where the CBM is shown in green color as the I electrons contribute the most to it. This is similar to the pressure-induced electronic structure transition from the insulating phase to the metal phase reported in Liang et al , showing a noticeably enhanced I-5p orbital contribution in the CBM under 50 GPa.…”
Section: Resultssupporting
confidence: 90%
“…Applying a hydrostatic pressure to a material can easily tune the material's various properties. [13][14][15] L. Wang et al reported on the inuence of lead halide perovskite CH(NH 2 ) 2 PbBr 3 and found that the structural phase is changed at 2.2 GPa. 16 Pressuredependent samples undergo band-gap energy shrinkage and the electron orbits move toward the electric eld.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exerting external pressure on perovskites and studying its effect on optoelectronic properties is a significant area of research. [36][37][38] Generally, within the same phase, upon compression, insulators and semiconductors show band gap decrement. This band gap decrement along with electron-electron correlations and electron-phonon coupling can also lead to metallization and eventually superconductivity.…”
Section: Introductionmentioning
confidence: 99%